اثير تدريبات الهيبوكسيك باستخدام وسيلة مساعدة على تطوير بعض المتغيرات الوظيفيه لعدائات 800م - زينب قحطان الهاشمي (الرياضة المعاصرة, 2015)
The sports training based on scientific grounds correct factors that increase and improve indicators functional and physical abilities and skills and thus improve sporting achievement, and aerobics are only cramps against opponents certain has been lengthened or shortened at the time of their performance and this depends on the objective of the training and capacity to be training. One of these training methods that have been associated athletics, especially 800 m hypoxic training to learn the extent of the impact of this type of training on functional variables if the body is exposed to an environment that is natural. Hence the importance of research in the use of means to help the performance of hypoxic training who works in the development of some of the variables functional 800-meter runners. Hence the problem of the research in the use of means to assist in the training and the use of hypoxic training method, and this could be the answer to the following question? Is the use of hypoxic training and working on a way to help develop some of the variables functional players 800 m. The study was conducted on the players club girl Baghdad (800 runners) and 8 of their number of players during the period from 13/02/2014 till 14/04/2014 The researcher used the experimental method and the sample are all one group trial by 8 players .autam indicators to measure the functional (self-mute and pulse rate and the number of breaths per minute). In the light of experience exploratory researcher prepared hypoxic training, by an aid device mute self, and applied within the training module for players, track and field club girl in Section intermediate rate (20 minutes) and by (3 units) per week at a rate of (90 minutes) of the unit and training for two months It is then carried out a posteriori tests results were statistically significant treatment system by SPSS. The researcher concluded that hypoxic training using an aid her active role in the development of some of the indicators of functional players 800 m. The researcher recommends exercises in hypoxic attention because of its active role in the development of functional indicators of the players and field effectiveness of 800 m.